JARINGAN INTERNET DAN SOSIAL MEDIA DALAM RANTAI PASOKAN DAN LOGISTIK: PERKEMBANGAN DAN TOPIK YANG MUNCUL - Ghozali Ghozali (STIE Mahardhika, 2020)
Although social media has been used in a number of business and science domains, its use and functionality in relation to the supply chain is still limited. This article explores the void and provides new evidence and original perspectives for this information agency and introduces current and contemporary developments and themes. Over a span of 4 months, we downloaded tweets #supply chain and/or #tagar logistics. After clearing data and filtering tweets in English, we analyzed 76,378 articles using various computational techniques. Our analysis reveals important developments taking place where a wide range of supply chain management technologies are in a dominant position to play. Blockchain is the world's leading platform followed by artificial intelligence. The improved logistics position of last mile also shows that it can be connected to e-commerce and customer support. Supply chain technology is also grouped and linked in similar dendrograms and, automation related to robotics and robotics, analytics is associated with results, artificial intelligence is linked to IoT and machine learning. Related relationships are highlighted by other developments affecting contemporary supply chains. This study offers feedback for supply chain management on important patterns and themes developing in their field, as well as new graphic metrics to consider the environmental topology of social network attitudes. These developments, in particular, will provide useful insights into how markets are evolving and help proactively determine future investment areas.